Interleukin‐17A and vascular remodelling in severe asthma; lack of evidence for a direct role. Issue 4 (20th February 2018) - Panariti, A.; Baglole, C. J.; Sanchez, V.; Eidelman, D. H.; Hussain, S.; Olivenstein, R.; Martin, J. G.; Hamid, Q.
Summary: Background: Bronchial vascular remodelling may contribute to the severity of airway narrowing through mucosal congestion. Interleukin (IL)‐17A is associated with the most severe asthmatic phenotype but whether it might contribute to vascular remodelling is uncertain. Objective: To assess vascular remodelling in severe asthma and whether IL‐17A directly or indirectly may cause endothelial cell activation and angiogenesis. Methods: Bronchial vascularization was quantified in asthmatic subjects, COPD and healthy subjects together with the number of IL‐17A + cells as well as the concentration of angiogenic factors in the sputum. The effect of IL‐17A on in vitro angiogenesis, cell migration and endothelial permeability was assessed directly on primary human lung microvascular endothelial cells (HMVEC‐L) or indirectly with conditioned medium derived from normal bronchial epithelial cells (NHBEC), fibroblasts (NHBF) and airway smooth muscle cells (ASMC) after IL‐17A stimulation. Results: Severe asthmatics have increased vascularity compared to the other groups, which correlates positively with the concentrations of angiogenic factors in sputum. Interestingly, we demonstrated that increased bronchial vascularity correlates positively with the number of subepithelial IL‐17A + cells. However IL‐17A had no direct effect on HMVEC‐L function but it enhanced endothelial tube formation and cell migration through the production of angiogenic factors by NHBE and ASMC. Conclusions & Clinical Relevance: Our results shed light on the role of IL‐17A in vascular remodelling, most likely through stimulating the synthesis of other angiogenic factors. Knowledge of these pathways may aid in the identification of new therapeutic targets.